Assessing Perlocutionary Effects Through Directive Speech Acts In An Autistic Child During Joint Comprehension Activities - Muhammad Nazrin Rosli; Afida Mohamad Ali; Ain Nadzimah Abdullah; Hamidin Awang; Shameem Rafik-Galea (Human Resource Management Academic Research Society, 2024)
The study analysed the perlocutionary effects elicited by an autistic child through the use of directive speech acts during joint comprehension activities. While studies related to ASD are largely conducted quantitatively, this study incorporated a case study method involving a Malaysian English speaking ASD child, to analyse the conversational interactions between the subject and the interlocutor during joint comprehension activities. This case study draws on Searle's (1975) framework, under which the speech acts are described alongside perlocutionary actions which are analysed through discourse analysis. The data of the case study was collected through audio/video recordings, and triangulated with observations during the joint comprehension activities, as well as interviews with the parents and teacher. The definitions and classifications of the disorder were reviewed from the first description by Kanner (1943) and the Theory of Mind (Leslie, 1987) interpretation of the core impairments in Autism, to the current 5th Diagnostic and Statistical Manual of Mental Disorders (DSM-V, 2013) classifications. Many patterns of communication arose from the use of the directive speech acts which impede and support interaction. Findings also revealed that specific communication skills used by the special needs facilitator have implications for communication in English where meaningful interactions can be formed with the Autistic child. This could help to create awareness among educators in designing special needs learning materials, especially in Malaysia.